2015
DOI: 10.1002/jcph.584
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic modeling and simulation for assessing renal impairment effect on the pharmacokinetics of mirogabalin

Abstract: A population pharmacokinetic model was developed to describe plasma concentrations of mirogabalin and lactam metabolite, obtained following a single oral dose of 5 mg mirogabalin to subjects with varying degrees of renal function.A 2-compartment model was used for both mirogabalin and lactam metabolite. Body weight was a significant covariate on volume of distribution of mirogabalin and lactam metabolite, whereas creatinine clearance significantly affected both renal and nonrenal clearance of mirogabalin. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…The results of the current study are also supported by those derived from the population PK model, which demonstrated that total mirogabalin clearance was reduced by 25%, 54%, and 76% in white subjects with mild, moderate, and severe renal impairment, respectively, relative to normal controls . Similar results were observed in the Japanese subjects enrolled in the current study; the cumulative percentage of dose excreted into urine decreased with increasing severity of renal impairment.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of the current study are also supported by those derived from the population PK model, which demonstrated that total mirogabalin clearance was reduced by 25%, 54%, and 76% in white subjects with mild, moderate, and severe renal impairment, respectively, relative to normal controls . Similar results were observed in the Japanese subjects enrolled in the current study; the cumulative percentage of dose excreted into urine decreased with increasing severity of renal impairment.…”
Section: Discussionsupporting
confidence: 87%
“…Given that mirogabalin is primarily eliminated in the urine, renal function can be expected to play a significant role in its elimination and clearance . A 2‐compartment population PK model — designed to describe the concentration–time profiles of mirogabalin 15 mg once or twice daily in European subjects with varying degrees of renal function — demonstrated that in white subjects, mirogabalin exposure increased with increasing degrees of renal impairment . Therefore, the current study evaluated the PK profile of mirogabalin in a cohort of Japanese subjects with varying degrees of renal impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When administered to healthy human subjects, it was also shown to exhibit linear absorption and plasma protein binding of 25% (Table 1) [30].…”
Section: Mirogabalinmentioning
confidence: 98%